Структурування ланцюга поставок у контексті ідентифікації джерел формування емерджентних властивостей - Фалович, Володимир Андрійович (Видавництво Львівської політехніки, 2017)
Проаналізовано управління ланцюгами поставок у структурі логістичних послуг вітчизняних підприємств й ідентифіковано базові характеристики сучасного ланцюга поставок. Встановлено, що глобалізація й інтернаціоналізація, зростаюча конкуренція і орієнтація на кінцевого споживача, розвиток інформаційно-комунікаційних технологій та електронної комерції окреслили значний потенціал розвитку ланцюгів поставок. Встановлено існування різних форм взаємовідносин між постачальниками та клієнтами, зміни бізнес-процесів, що зумовлені впровадженням у функціонування ланцюга поставок сучасних інформаційних технологій. Оцінено його структуру у контексті ідентифікації джерел формування емерджентних властивостей.

It is made the analysis in managing of supply chain in the structure of domestic enterprises and it is identified the basic characteristics of the modern supply chain: creating of additional value in each of its link (stages of products creation or services); integrated properties; orientation of all participants in the supply chain on common result – to satisfy end-user; global character. It is identified the meaning of concepts which are closed in meaning to the term “supply chain” and it is found that the semantic content of these terms depends upon: the type of market in which the organization operates its activity; and upon the brunch where it operates; particular positions of the organization; the maturity of economic relations in the country. It is found that globalization and internationalization, increased competition and focus on the end consumer, the development of ICT and e-commerce outlined the great potential of the supply chain. It is determed the existence of different forms of relationships between suppliers and customers, and changes in business processes, which are caused by the implementation of supply chain functioning of modern information technologies. It is proved that the material, information and financial flows should be considered as integrators of supply chain, which provide its origin emergent properties. Connections are usually established between components and process control levels of each participant in order to facilitate the free flow of data between them. Coordination of partners actions in the supply chain is achieved when each participant, making decisions, acts rationally, taking into account the needs and capabilities of all partners and the supply chain as a whole. Coordination is a necessary condition for achieving the common goal of supply chain as a whole and all its parts. It is established that receiving of such properties in the supply chain as emergence is not possible, if not eliminate all possible conflicts that may arise between partners in the supply chain (between the manufacturer and the carrier between the carrier and distributor between the supplier, manufacturer, carrier and distributor). Increased dependence of partners in the supply chain increases the degree of risk and uncertainty at a time of rising profits. To solve these problems, supply chain members should strive for maximum interaction and coordination of their actions to with each other. This supply chain partners are required to identify coordination mechanisms that will help to reduce uncertainty in the supply chain and ensure coordination of all partners in it, including the rational reallocation of resources and at the same time, the rapid formation of strategy and tactics of behavior in the market using global trends to their advantage. The following of such conditions will improve the efficiency of the supply chain, increasing its maximum emergence.
Structuring of the supply chain identification in the context sources of emergent properties
Keywords: ланцюг поставок; інвестиційні товари; аутсорсинг; інформаційні технології; координація; перерозподіл ресурсів; емерджентність; supply chain; capital goods; outsourcing; information technology; coordination; reallocation of resources; emergence; 658.7; 001.895